Chinese Herbal Extracts Exert Neuroprotective Effect in Alzheimer’s Disease Mouse Through the Dopaminergic Synapse/Apoptosis Signaling Pathway - Huang, Qianqian; Zhang, Chen; Qu, Sihao; Dong, Shi; Ma, Qihong; Hao, Ying; Liu, Zimin; Wang, Shanglong; Zhao, Haibin; Shi, Yuanyuan (Frontiers in Pharmacology, 2022)
Background: Alzheimer’s disease (AD) as an age-related, irreversible neurodegenerative disease, characterized by cognitive dysfunction, has become progressively serious with a global rise in life expectancy. As the failure of drug elaboration, considerable research effort has been devoted to developing therapeutic strategies for treating AD. TCM is gaining attention as a potential treatment for AD. Gastrodia elata Blume, Polygala tenuifolia Willd., <ext-link ext-link-type="uri" xlink:href="https://mpns.science.kew.org/mpns-portal/plantDetail?plantId=723155&query=%E8%82%89%E8%8B%81%E8%93%89&filter=&fuzzy=false&nameType=all&dbs=wcsCmp" xmlns:xlink="http://www.w3.org/1999/xlink">Cistanche deserticola Ma, Rehmannia lutinosa (Gaertn.)DC., Acorus gramineus Aiton, and Curcuma longa L. (GPCRAC) are all well-known Chinese herbs with neuroprotective benefits and are widely used in traditional Chinese decoction for AD therapy. However, the efficacy and further mechanisms of GPCRAC extracts in AD experimental models are still unclear. The purpose of this study was to investigate the synergistic protective efficacy of GPCRAC extracts (composed of extracts from these six Chinese medicines), and the protein targets mediated by GPCRAC extracts in treating AD. Methods: Scopolamine-induced cognitive impairment mouse model was established to determine the neuroprotective effects of GPCRAC extracts in vivo, as shown by behavioral tests and cerebral cholinergic function assays. To identify the potential molecular mechanism of GPCRAC extracts against AD, label-free quantitative proteomics coupled with tandem mass spectrometry (LC-MS/MS) were performed. The integrated bioinformatics analysis was applied to screen the core differentially expressed proteins in vital canonical pathways. Critical altered proteins were validated by qPCR and Western blotting. Results: Administration of GPCRAC extracts significantly recovered scopolamine-induced cognitive impairment, as evidenced by the improved learning and memory ability, increased Ach content and ChAT activity, as well as decreased AchE activity in the hippocampus of mice. In total, 390 proteins with fold-change>1.2 or <0.83 and p < 0.05 were identified as significant differentially expressed proteins, of which 110 were significantly up-regulated and 25 were significantly down-regulated between control and model group. By mapping the significantly regulated proteins, we identified five hub proteins: PPP2CA, Gsk3β, PP3CC, PRKACA, and BCL-2 that were associated with dopaminergic synapse and apoptosis signaling pathway, respectively. Western blotting and QPCR demonstrate that the expression levels of these core proteins could be significantly improved by the administration of GPCRAC extracts. These pathways and some of the identified proteins are implicated in AD pathogenesis. Conclusion: Administration of GPCRAC extracts was effective on alleviating scopolamine-induced cognitive impairment, which might be through modulation of dopaminergic synapse and apoptosis signaling pathway. Consequently, our quantitative proteome data obtained from scopolamine-treated model mice successfully characterized AD-related biological alterations and proposed novel protein biomarkers for AD.